Psychometric properties of the Parent-Report Version of the UCLA PTSD Reaction Index for DSM-5 - Ramos, C.; Cabral, E.; Serrão, V.; Figueira, P.; Santos, P. V.; Baptista, J. (Journal of Child and Adolescent Trauma, 2022)
The UCLA PTSD Reaction Index for DSM-5 (RI-5) is a developmentally appropriate and well recognized screening tool for the assessment of Post-Traumatic Stress Disorder (PTSD) in children and adolescents. The children/adolescent self-report version of the RI-5 has been thoroughly studied in very recent years, showing adequate psychometric properties. Despite such results, the utility of the parent/caregiver-report version, which also integrates the RI-5 system, remains to be explored. As such, the present study aimed to test the general psychometric properties of the parent/caregiver-report version of RI-5, based on a sample of 457 children and adolescents, aged between 7 and 17 years, exposed to at least one potentially traumatic experience, and their respective primary caregivers. The RI-5 total score and categories revealed good internal consistency reliability. The total number of traumas reported emerged as a significant predictor of the RI-5 total score. The RI-5 total score proved to be significantly correlated with more internalizing and externalizing problems, but correlation coefficients were below .70, serving as an indicator of discriminant validity. The four-factor structure of the RI-5 was supported through confirmatory factor analysis. In conclusion, the present study provided preliminary evidence supporting the utility of the parent/caregiver-report version of the RI-5 for research purposes and for clinical assessment and treatment, anchored on a multiple informant perspective of child psychopathology.